Burns Wound Healing Activity of Extract Gel Formula of Lidah Buaya (Aloe vera) and Senggani Leaf (Melastoma polyanthum): Aktivitas Penyembuhan Luka Bakar Formula Gel Ekstrak Lidah Buaya (Aloe vera) dan Daun Senggani (Melastoma polyanthum) - Wahyuningsih, Sri; Syamsu, A. Suparlan Isya; Awaluddin, Nurhikma; Andriawan, Riki (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Aloe vera and senggani leaf can accelerate tissue regeneration, re-epithelialization, fibroblast stimulation, and collagen formation in the skin for burns wound healing. Burns wound can cause damage in the capillaries of the skin, then Aloe vera and senggani leaf were formulated into the gel formula for burns wound healing. The gel has the advantage of high water content; then it will hydrate the epidermis layer, increasing the penetration of the active substances. This study aims to formulate a gel of extract Aloe vera and senggani leaf (Melastoma polyanthum) and to evaluate the burns wound healing activity. The gel was formulated by composition of Aloe vera : senggani leaf with concentrations (0.5%: 1%); (0.5% : 3%); and (0.5% : 5%). Burns wound healing activity was observed by the diameter of the burn wound. The result showed that the gel with a concentration of (0.5%: 5%) gave a significance value of 0.692 (p >0.05) against positive control, then it was the formula that effective for burns wound healing.